Pressure injury prevention in the perioperative setting: An integrative review - Isabel Wang; Rachel Walker; Brigid Gillespie (Journal of Perioperative Nursing)
Background: Pressure injury (PI) has a significant impact on patients and their families, and is costly to health care institutions. Perioperative PI remains problematic, although little is reported about current perioperative pressure injury prevention (PIP) strategies.